Improved uptake of climate smart rice varieties with high potential for marketability in Mali - Dossou-Yovo, Elliott Ronald; Guindo, Samuel; Koné, Pierre; Akpoffo M, Marius; Doumbia, Salif (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This research examined the dissemination mechanisms of climate smart rice varieties, its impact on rice yield, farmers' income, and food consumption score, as well as the farmers' perception of their advantages in Mali. In total, 35,280 farmers adopted the climate smart rice varieties promoted by the AICCRA project on a total area of 19,404 ha. The primary dissemination methods included on-farm demonstrations, farmers field days and capacity building of seed producing companies. The adoption of climate smart rice varieties increased farmers’ yield by 1.3 – 1.5 t/ha and income by 365 – 511 USD/ha. The food consumption of farmers adopting climate smart rice varieties was significantly increased. In total, the adoption of climate smart rice varieties increased the production of rice by 28,446 ton and farmers’ income by 7.6 million USD. When farmers were queried about the advantages of climate smart rice varieties, they highlighted an increase in their climate resilience due to the ability of the rice varieties to withstand the challenges posed by climate change, such as extreme temperatures, erratic precipitation, and increased frequency of droughts and floods. They also mentioned higher resource use efficiency due to the more efficient use of water and nutrients. Farmers further reported that the climate smart rice varieties had a shorter growth duration, and mentioned their community resilience to climate-induced shocks has increased. Therefore, farmers mentioned that climate-smart rice varieties play a critical role in ensuring food security by offering a reliable and resilient source of sustenance in the face of climatic uncertainties and challenges in rice production.